Analysis of Quality Assurance Performance in the Application of Manual Testing and Automation Testing for Software Product Testing - Safaat, Gesang; Utami Tjhin, Viany (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This paper aims to understand the influence of using the Katalon tool in application testing, comprehend the testing scenario process using Katalon, and compare it with manual testing. The testing process using Katalon Studio follows the design proposed by the author based on references from previous literature. The research method employed includes literature review, test case collection and analysis, implementation, test case testing, and evaluation of implementation results. Katalon can be utilized for testing using test cases. These test cases are recorded and replayed by capturing each response in a single event in the application. Both automated testing and manual testing were conducted using nine scenarios consisting of Crypto Asset Search, Limit Order Method for Buying and Selling Crypto Assets, Instant Order Method for Buying and Selling Crypto Assets, Crypto Asset Deposit and Withdrawal Address Method, Crypto Asset Username Deposit and Withdrawal Method, Failed Crypto Asset Purchase with Limit Order Method, Failed Crypto Asset Sale with Limit Order Method, Failed Crypto Asset Purchase with Instant Order Method, and Failed Crypto Asset Sale with Instant Order Method. The average comparison of the nine scenarios tested using manual and automated methods shows a difference of 11.04%. Therefore, automated testing is 11.04% faster than manual testing. The conclusion drawn from this research is that testing using Katalon is shorter compared to manual testing using the same test case.